PENGARUH PEMUPUKAN LEWAT DAUN DAN WAKTU DEFOLIASI PADA PERTUMBUHAN DAN HASIL JAGUNG (Zea mays L.) VARIETAS NASA 29 - Asep Pebriandi; Muhammad Amin (Agrotechnology Innovation (Agrinova), 2021)
This study aims to determine the effect of foliar fertilization and corn leaf trimming (defoliation) on the growth and yield of hybrid corn NASA 29. This research was conducted at the Samboja Experimental Garden, Bukit Raya Village, Kec. Samboja, Kutai Kartanegara, East Kalimantan, in April-July 2020. The planting material used was the NASA 29 hybrid corn variety, KNO3 fertilizer, Gandasil D fertilizer, MKP fertilizer. This study used a factorial randomized block design (3 X 3) with 3 (three) replications. The first factor was the type of fertilizer that was applied through the leaves (foliar) which consisted of 3 levels, namely P1 (fertilizer gandasil), P2 (fertilizer MKP), and P3 (fertilizer Rosasol) with a dose of 10 grams/liter each given at the age of 65 DAS. The second factor was defoliation time which consisted of 3 levels, namely D1 (75 days after planting), D2 (defoliation at 82 days after planting), and D3 (defoliation at 90 days after planting). The observed data were analyzed by means of the analysis of variance with the F test at α 5%. if there is a significant difference, it is followed by the Honestly Significant Difference (HSD) test at α 5%. The results showed that the treatment of the type of fertilizer through the leaves and defoliation along with the interactions had no significant effect on the variables of plant height, ear length, and ear diameter, while the treatment of fertilizers by leaf and defoliation and their interactions had no significant effect on the variables of plant height, stem diameter. ear length and ear diameter. P3 fertilizer treatment and defoliation at the age of 82 days after planting (D2) gave the best results on the variable ear weight and dry seed weight.